Reaching those with the greatest need: How Australian primary health care service managers, practitioners and funders understand and respond to health inequity - Freeman, T.; Baum, F.; Lawless, A.; Jolley, G.; Labonte, R.; Bentley, M.; Boffa, John (2011)
Equity of access to services and in health outcomes are key goals of primary health care. This study considers understandings of equity and perceptions of current performance in relation to equity among primary health care service staff, health service executives and funders. Semi-structured interviews were conducted with managers, practitioners and administration staff at five primary health care services in Adelaide and one in Alice Springs, as well as with South Australian funders and regional health service executives (n = 68). Services were responding to health inequity by taking actions to improve equitable access to their service, facilitating equitable access to health care more generally, and advocating and taking action on the social determinants of health inequities. As well as availability, affordability and acceptability, our analysis indicated a fourth dimension of equity of access we named 'engagement'. Our respondents were less able to point to examples of advocacy or action on the social determinants of health inequities than they were to examples of actions to improve equity of access. These findings indicate current strengths and also scope to encourage a broader and more comprehensive role for primary health care in addressing health inequities. © 2011 La Trobe University.